Plagiarism and Originality - Diffusionism in the Study of the History of Cookery - Mennell, Stephen (Petits Propos Culinaires, 2001)
This piece is a bibliographic oddity. It constitutes a paper given by Stephen Mennell at the Oxford Symposium in 1984. It was not included in the published proceedings because it was erroneously thought to have been put into print elsewhere. When looking it out for purposes of citation, Mennell was aghast to find it had never in fact been published and, thinking the arguments retained much of their force, proposed it for PPC. Readers should note that it antedates the author’s All Manners of Food (currently, the second edition, Illinois, 1996). It is concerned with the issues of originality, borrowing, plagiarism, authorship in cookbook writing and publishing